Diabetes and hypertension increase the placental and transcellular permeation of the lipophilic drug diazepam in pregnant women - Lalic-Popovic, M.; Paunkovic, J.; Grujic, Z.; Golocorbin-Kon, S.; Al-Salami, Hani; Mikov, Momir (BioMed Central Ltd, 2013)
Background: Previous studies carried out in our laboratories have demonstrated impaired drug permeation in diabetic animals. In this study the permeation of diazepam (after a single dose of 5 mg/day, administered intramuscularly) will be investigated in diabetic and hypertensive pregnant women.Methods: A total 75 pregnant women were divided into three groups: group 1 (healthy control, n = 31), group 2 (diabetic, n = 14) and group 3 (hypertensive, n = 30). Two sets of diazepam plasma concentrations were collected and measured (after the administration of the same dose of diazepam), before, during and after delivery. The first set of blood samples was taken from the mother (maternal venous plasma). The second set of samples was taken from the fetus (fetal umbilical venous and arterial plasma). In order to assess the effect of diabetes and hypertension on diazepam placental-permeation, the ratios of fetal to maternal blood concentrations were determined. Differences were considered statistically significant if p=0.05.Results: The diabetes and hypertension groups have 2-fold increase in the fetal umbilical-venous concentrations, compared to the maternal venous concentrations. Feto: maternal plasma-concentrations ratios were higher in diabetes (2.01 ± 1.10) and hypertension (2.26 ± 1.23) groups compared with control (1.30 ± 0.48) while, there was no difference in ratios between the diabetes and hypertension groups. Umbilical-cord arterial: venous ratios (within each group) were similar among all groups (control: 0.97 ± 0.32; hypertension: 1.08 ± 0.60 and diabetes: 1.02 ± 0.77).Conclusions: On line with our previous findings which demonstrate disturbed transcellular trafficking of lipophilic drugs in diabetes, this study shows significant increase in diazepam placental-permeation in diabetic and hypertensive pregnant women suggesting poor transcellular control of drug permeation and flux, and bigger exposure of the fetus to drug-placental transport.